Design of a simple and low cost electrical property tester for graphene material : a preliminary study. (March 2020) - Hidayat, Rahmat; Oktasendra, Fandi
Abstract: A simple and low cost electrical property tester for material has been designed and built using cheap components. This instrument consists of simple adjustable current source circuit using LM317, gold coated pin probe and multimeters. The circuit arranged has produced sufficient current to do an electrical property measurement. Value of current could be adjusted to select suitable current in measurement. Resistance vs current graph shows a reciprocal function that generated by a constant voltage of 1.25 volts in output pin. An experiment to examine sheet resistance of ITO glass was carried out to make sure the instrument work properly.